From earthquake swarm to a main shock–aftershocks: the 2018 activity in West Bohemia/Vogtland. Issue 3 (4th November 2020) - Bachura, M; Fischer, T; Doubravová, J; Horálek, J
SUMMARY: In earthquake swarms, seismic energy is released gradually by many earthquakes without a dominant event, which offers detailed insight into the processes on activated faults. The swarm of May 2018 that occurred in West Bohemia/Vogtland region included more than 4000 earthquakes with M L = 〈0.5, 3.8〉 and its character showed significant changes during the two weeks duration: what started as a pure earthquake swarm ended as a typical main shock–aftershock sequence. Based on precise double-difference relocations, four fault segments differing in strikes and dips were identified with similar dimensions. First, two segments of typical earthquake swarm character took place, and at the end a fault segment hosting a main shock–aftershock sequence was activated. The differences were observable in the earthquakes spatio-temporal evolutions (systematic versus disordered migration of the hypocentres), b-values (>1.3 for the swarm, <1 for the main shock–aftershocks), or the smoothness of seismic moment spatial distribution along the fault plane. Our findings can be interpreted by local variations of fault rheology, differential stress and/or smoothness of the faults surface, possibly related to the crustal fluids circulating along the fault plane and their interplay with the seismic cycle.